Experimental measuring set‐up and procedure for the traction coefficient on roller‐on‐disc contact. (4th February 2016) - Gama, A.; Cousseau, T.; Graça, B.; Castro, J.; Seabra, J.
Abstract: A pin‐on‐disc machine was modified to measure traction coefficient and the potential of contact difference under controlled conditions of slide‐to‐roll ratio, temperature, contact pressure and entrainment speed; oil, grease, grease's base oil and bleed‐oil were tested. This new arrangement proved to be efficient to characterise lubricants traction behaviour, film separation and tribofilm generation. Copyright © 2016 John Wiley & Sons, Ltd.